Pemanfaatan Pojok Baca untuk Menumbuhkan Minat Baca Anak Usia Dini - Nia Inamia; Herwina Herwina; Asri Neli Putri (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
The purpose of this study was to determine and describe the use of reading corners to foster reading interest among 15 children in the Mawar group at Permata Bunda Kindergarten, Pulau Sarak Village. This research method is qualitative, with data collected through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and triangulation for validation. The results of the study indicate that the use of reading corners that are managed neatly, attractively, and comfortably is effective in increasing children's interest in reading. This is evidenced by the enthusiasm of children visiting the reading corner during playtime, interest in reading books independently, and active participation in reading activities 10 minutes before learning. The contribution of this study for teachers regarding the use of reading corners is that teachers must also serve as good role models, modeling for children to love reading books. It is recommended that teachers continue to motivate and actively involve children to maintain the consistency of their interest in reading.